Pola Perilaku Pencarian Informasi Dosen Pembelajaran Jarak Jauh Dalam Perspektif Leckie di Era New Normal - Habiburrahman Habiburrahman (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
The policy taken by the state regarding the education sector is implementing distance learning (online learning). Thus both students, students, teachers, and lecturers must adapt to these conditions so that learning continues to run as it should. In relation to this phenomenon, the purpose of this research is to identify and describe models of information-seeking behavior, especially by Distance Learning Lecturers or (PJJ) at the Faculty of Law, Sosial and Political Science (FHISIP), Universitas Terbuka in meeting their information needs. The research used descriptive qualitative design. The subjects in this study were FHISIP Lecturers at the Universitas Terbuka while the object was the information seeking behavior of FHISIP Lecturers at the Open University. Overall, the data analysis technique performed begins with data collection, data reduction, data presentation, and drawing conclusions. As for data validation, researchers used triangulation. This research found that the roles and tasks carried out by the pjj lecturers sequentially are: as educators, researchers, and community service as well as carrying out activities to support distance learning. Of all these roles, the intensity of information seeking is highest in the first role, namely as an educator because the process of fulfilling information needs is carried out every day and The characteristics of the information needs of informants as a whole are based on age, area of specialization, recent education and experience. Based on these factors, it can be concluded that senior informants have a wider range of information needs than junior informants.